2022
DOI: 10.4081/dr.2022.9492
|View full text |Cite
|
Sign up to set email alerts
|

Mortality risk factors in febrile ulceronecrotic Mucha- Habermann disease: a systematic review of therapeutic outcomes and complications

Abstract: Febrile ulceronecrotic Mucha-Habermann disease (FUMHD) is a variant of pityriasis lichenoides et varioliformis acuta (PLEVA). Although rare, the condition may progress to involve serious complications and even lead to fatal outcomes if diagnosis and appropriate treatment is delayed. A PubMed search following Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRIMSA) guidelines was performed to find cases of FUMHD from the earliest records to October 2021. Treatments, complications, and patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 70 publications
0
4
0
Order By: Relevance
“…In more than one case that failed initial systemic therapy, MTX showed excellent results [38,6]. Another recent systematic review that includes children and adults focused on mortality risk factors in FUMHD and therapeutic outcomes and complications [39].…”
Section: Case Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In more than one case that failed initial systemic therapy, MTX showed excellent results [38,6]. Another recent systematic review that includes children and adults focused on mortality risk factors in FUMHD and therapeutic outcomes and complications [39].…”
Section: Case Discussionmentioning
confidence: 99%
“…Both pediatric and adult patients with a FUMHD mortality risk score 10 may benefit from an early transfer to an appropriate intensive care unit. Later, a systematic review found no association of mucosal involvement and mortality risk [39]. Also, monoclonal T cell receptor rearrangement was generally associated with a higher mortality risk [10].…”
Section: Case Discussionmentioning
confidence: 99%
See 2 more Smart Citations